A study of the heroine in certain Victorian novels - Addecott, Grahame John (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1959)
During the reign of Queen Victoria was seen the gradual emergence of the emancipated woman. The idea that women were innocent beings who must be kept from real knowledge of the world died hard, however, and to the end of the era there were many who repudiated the very concept of emancipation whether in literature or life. Coupled with the chivalrous, idealistic concept of womanhood was Victorian respectability, and it is not surprising that in the earlier Victorian novels we see clearly the idealistic concept of women and the effects of the cult of respectability. To illustrate my theme, of the gradual change in the concept of the novel which naturally kept pace, more or less, with the progress the emancipation of women was making, I have chosen one novel from each of seven great Victorian novelists whose works span the whale era. The only exception I have made is with Charlotte Bronte. In her case the heroines of two of her novels are discussed mainly because she is the first Victorian novelist to sound a note of protest against the then conventional concept of the heroine.
Keywords: English fiction -- 19th century -- History and criticism; Heroines in literature